Effect of sharia-based nursing care using swanson's caring model (ShariaSwanCare) on patient satisfaction: a quasi-experimental study - Hadi, Muhammad; Mulyani, Sri; Li Yoong , Tang; Widiastuti , Eni; Kartika, Rini Fatma; Hasanah, Idyatul (Jurnal Ners, 2025)
Introduction: This study aimed to evaluate the effect of Sharia-Based Nursing Care, utilizing Swanson’s Caring Model (ShariaSwanCare), on patient satisfaction in hospital settings. Methods: A quasi-experimental pretest–posttest design with a control group was employed, involving 76 hospitalized patients (38 per group) selected via purposive sampling. Participants received a structured, five-day treatment for conditions such as hypertension, diabetes mellitus, cerebrovascular accident (stroke), and pneumonia. Eligibility criteria included compos mentis status and uninterrupted completion of the five-day treatment period. Patients who were transferred to other wards were excluded. The intervention group received ShariaSwanCare, administered daily for five consecutive days, with patient satisfaction assessed every 24 hours. The control group received standard hospital care without additional interventions. Data were analyzed using both paired t-tests and independent t-tests. A significance level of p < 0.05 was used for all analyses. Results: Statistical analysis yielded a p-value of < 0.001, indicating that the implementation of ShariaSwanCare had a significant positive effect on patient satisfaction. Specifically, patients in the intervention group showed a greater increase in satisfaction scores compared to the control group. The paired t-test revealed a significant improvement from pre- to post-intervention in both groups, but the effect was more pronounced in the intervention group. Conclusions: Sharia-based nursing practices, when integrated with Swanson’s Caring Model, can effectively enhance patient satisfaction. With appropriate training and structured implementation, these practices have the potential to be adopted across Islamic hospitals.